ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI GOING CONCERN (Studi pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2012-2014) - Agil Priambodo, 11.05.52.144; Alfasadun, Alfasadun (Students Journal of Economic and Management, 2016)
The aim of this study was to analyze the effect of audit quality, leverage, earnings growth, profitability and the size of the company going concern audit opinion on the companies listed on the Stock Exchange Year 2012-2014. The population in this study are all companies listed on the Indonesian Stock Exchange (BEI). The sample in this study as many as 28 companies. The sampling technique used purposive sampling. The criteria for the sample in this research is the company to use the Indonesian Rupiah and the company has experienced a loss of at least one financial reporting period during the observation period 2012-2014. The analytical tool used is multiple linear regression. Results of the analysis can be concluded that: Quality audit does not affect the going concern audit opinion. Leverage positive effect on the going concern audit opinion does not affect the profit growth going concern audit opinion. Profitability negatively affect the going concern audit opinion. Company size does not affect the going concern audit opinion. Â Keywords: quality audit, leverage, earnings growth, profitability, size and revenues going concern audit opinion